Cardiac and Arterial Baroreceptor Function in Heart Failure - Zucker, Irving H. (Journal of Basic and Applied Pharmacology, 2015)
Although the condition of heart failure can be defined in hemodynamic terms, it is an oversimplification to think that the systemic consequences of this disease entity is due solely to alterations in peripheral blood flow. Clearly, neurohumoral events can play a major role in the compensatory adjustments which take place in heart failure, albeit at the expense of a deterioration in organ function. Many of the normally occurring neurohumoral control mechanisms are abnormal in heart failure. These come about from changes in both efferent and afferent components of the reflex arcs. The fact that sensory endings in the heart and blood vessels may play an important role in the abnormal reflex control of the circulation in heart failure has not been generally appreciated. There is a good deal of clinical and animal studies that suggest that mechanoreceptor function in the atria, ventricles, aorta and carotid sinus is abnormal in heart failure. In most cases these receptors function at a depressed sensitivity with the possible exception of left ventricular receptors. The mechanism (s) that are responsible for the observed receptor abnormalities in heart failure are not completely understood, however at this point it is reasonable to assume that both structural and compliance changes may be operative to cause the abnormalities observed for atrial receptors. The cause of the decrease in arterial baroreceptor discharge sensitivity is not known, however we do know that it is not due to a change in compliance of the carotid sinus or aortic arch. Possibilities which need to be investigated include alterations in sympathetic control of baroreceptor discharge and changes in Na-K pump activity in the baroreceptors themselves. As far as ventricular receptors are concerned we do not currently have enough data to determine the mechanism of the enhanced reflex changes that are evoked from their stimulation in heart failure.